On the Transition From Precursors to the Initial Upward Positive Leader in Negative Rocket‐Triggered Lightning. Issue 17 (26th August 2021) - Li, Xiao; Lu, Gaopeng; Jiang, Rubin; Zhang, Hongbo; Fan, Yanfeng; Shi, Tao; Qie, Xiushu; Zhang, Yang; Ren, Huan; Zhang, Chenxiao; Zhang, Yijun
Abstract: Precursory current pulses (precursors) and initial upward leader pulses are examined to characterize the charge transfer of precursors and the sustained upward leader during the early stage of rocket‐triggered lightning. According to the analysis of six negative triggered flashes, it is found that both precursors and the initial upward positive leader (iUPL) pulse are led by a small deflection that appears at about 25 μs prior to the major pulses. The characteristics of precursors and iUPL pulses are very similar except that the precursors generally transfer less electric charge (35.07 μC on average) than iUPL pulses do (64.73 μC on average). Some marginal differences in the parameters (e.g., rise time, duration) may be attributed to the modification of the current pulses caused by the different impedances of the leader channel and the steel wire. The ascending rocket causes the enhancement of electric field ( E ‐field) in the close vicinity of the wire tip, and therefore the breakdown of the iUPL is initiated by a stronger E ‐field than that of the precursors. The step lengths of the precursors (defined as the extended length of the wire tip lifted by the rocket between two adjacent isolated precursors) are similar to that of iUPL pulses. Our analyses indicate that the transition from precursors to the iUPL occurs when the E ‐field around the wire tip is strong enough, by the accumulation of more positive charge, to launch a meter‐scale breakdown and the ensuing charge transfer to ground. Plain Language Summary: For classical rocket‐and‐wire triggered lightning, an interesting question that is also of practical concern is under what conditions will intermittent precursors transition into a sustained initial upward leader, which is critical to understanding the inception of a lightning leader. Similarities in waveforms and parameters imply that the discharge processes of precursors and the initial upward leader are similar. A new finding of our analysis with respect to several negative triggered lightning flashes is that the first distinct pulse of all precursors and of the initial upward positive leader is always preceded by a small deflection, which clarifies the poorly understand behavior of discharges observed with the very high‐frequency interferometric mapping technique. We show that there are several similarities between precursors and the iUPL, such as pulse duration, pulse rise time, peak amplitude of current pulses, and step length. However, the amount of charge transferred by individual precursor pulses is only half of that transferred by the iUPL pulses, which is likely related to the stronger E‐field at the higher altitude. Our analysis may provide an insight into the commonality and divergence of the discharge process at the stages of precursors and the iUPLs. Key Points: Both precursor discharges and the initial upward leader begin with a small pulse that leads the subsequent major pulses by about 25 μs The charge transferred by individual precursor current pulses is significantly smaller than that by the current pulse of the iUPLs A relatively long quiet phase might indicate the development of clustered precursors or iUPLs rather than isolated precursor discharges